Influence of caffeic acid and Bacillus coagulans supplementation on growth, digestive enzymes, immune response, and antioxidant gene expression in common carp (Cyprinus carpio) and its resistance to Aeromonas hydrophila infection - Seyedeh Shiva Alavinejad; Mehdi Soltani; Seyed saeed Mirzargar; Poulin Shohreh; Ali Taherimirghaed (Aquaculture Reports)
Present study aimed to investigate the efficacy of dietary supplementation with caffeic acid and Bacillus coagulans on growth performance, digestive enzymes, and immunity of common carp (Cyprinus carpio), and also fish resistance against Aeromonas hydrophila. Fish (21.0 ± 0.5 g) divided into four groups: control group (CD, commercial basal diet), caffeic acid (CA, 5 g/kg feed), B. coagulans (BC, 2×107 CFU/g feed), and CA+BC (5 g/kg + 2×107 CFU/g feed) for 8 weeks, followed by a 14-day challenge with A. hydrophila. A significant enhancement was obtained in growth performance of all treated groups compared to CD (P < 0.05). Also, feed conversion ratio was significantly reduced in treated fish compared to CD group (P < 0.05). Fish of BC and CA+BC groups revealed an increase in activity of amylase, lipase, protease, trypsin, and chymotrypsin in the intestinal tissue. In addition, amylase, lipase, protease, and trypsin in CA group exhibited a higher activity than CD (P < 0.05). A lower decrease in aspartate aminotransferase and a higher increase in alkaline phosphatas were observed in BC and CA+BC groups than CD group (P < 0.05). Values of total protein, total immunoglobulin, lysozyme activity, and alternative complement pathway (ACH50) were higher in sera of BC and CA+BC groups than CD (P < 0.05). Additionally, expression of genes related to lysozyme, IL-1β, IL-8, TNF-α, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) in liver tissues of treatment groups were upregulated better than CD (P < 0.05). Furthermore, a significant reduction in mortality was observed in treatment groups compared to CD under the A. hydrophila challenge. These results exhibited that including a combination of caffeic acid and B. coagulans as functional dietary supplements in diet favors common carp health status and growth and, thus, can be recommended in the fish diet.